Pilgrimage Tourism of Dakshainkali - Kafle, Dol Raj (Patan Prospective Journal, 2022)
This study deals with the pilgrimage tourism in Dakshinkali, a famous Hindu temple in the southern part of the Kathmandu Valley, and the development of the region as an important pilgrimage tourism destination. This place is called Dakshinkali because the temple of Goddess Kali is on the south side of Kathmandu city. Goddess Kali as power is considered to be another form of Mother Parvati. Although Kali Devi has been established and worshiped in this place since ancient period, the importance of this place increased after the reign of the king Pratap Malla. At present, local products have found a good market because of as the number of pilgrimage tourists are increasing in Dakshainkali. Employment has also increased. Hotels and restaurants are well run. The living standard of the locals has increased as their income has increased. The increase in local government revenue has had a positive impact on the development of the Dakshainkali area. The main objective of this study is to introduce the importance of pilgrimage tourism of Dakshainkali. This article is mainly based on primary sources and also tries to make realistic by using some helpful secondary sources.